Case Report: Prominent Brainstem Involvement in Two Patients With Anti-CASPR2 Antibody-Associated Autoimmune Encephalitis - Liu, Pei; Bai, Miao; Ma, Chao; Yan, Yaping; Zhang, Gejuan; Wu, Songdi; Li, Zunbo; Zhao, Daidi; Ren, Kaixi; Li, Hongzeng; Guo, Jun (Frontiers in Immunology, 2021)
Anti-contactin-associated protein-like 2 (CASPR2) antibody-associated autoimmune encephalitis is commonly characterized by limbic encephalitis with clinical symptoms of mental and behavior disorders, cognitive impairment, deterioration of memory, and epilepsy. The classical lesions reported are located at the medial temporal lobe or hippocampus, whereas prominent brainstem lesions have not been addressed to date. Herein, we reported two patients mimicking progressive brainstem infarction with severe neurological manifestations. On brain magnetic resonance imaging (MRI) prominent brainstem lesions were noted, although multifocal lesions were also shown in the juxtacortical and subcortical white matters, basal ganglia, hippocampus, and cerebellar hemisphere. Unexpectedly and interestingly, both cases had detectable CASPR2 antibodies in sera and an exclusive IgG1 subclass was documented in the further analysis. They were treated effectively with aggressive immunosuppressive therapies including corticosteroids, intravenous immunoglobulin G and rituximab, with the first case achieving a rapid remission and the other undergoing a slow but gradual improvement. To the best of our knowledge, this is the first report on prominent brainstem involvement with definite MRI lesions in anti-CASPR2 antibody-associated autoimmune encephalitis, which helps to expand the clinical spectrum of this rare autoimmune disease and update the lesion patterns in the CNS.